Prevalence of traumas and PTSD in psychiatric population in Iceland - Lilja Dís Ragnarsdóttir 1985- (2018)
Increasing number of research has shown that the prevalence rate for traumas and PTSD are much higher than previously estimated, especially among the psychiatric population. The current study was a non-experimental cohort study with three main goals. The first goal was to assess the prevalence rate of traumatic events in the psychiatric population that seeks help at the psychiatric ward at Landspitali, the National university hospital of Iceland. The second goal was to assess the prevalence rate of PTSD in the same population. The third goal was to examine trauma disclosure and treatment history. The study was a pilot study for a larger ongoing research conducted in Iceland with the aim of gathering more knowledge on prevalence rate for traumas and PTSD within the psychiatric population in Iceland. The study was conducted over three weeks from the 12th of April to 3rd of May 2018. Participants were all patients receiving service at the psychiatric hospital in Iceland, total of 29. The majority of them were females (n=21). The age range was 20-55 years with the mean age of 31.2 years. Overall the results showed that 92,9% of participants reported having directly or indirectly experienced a traumatic event in their lifetime. The most commonly reported traumatic experience for women was sexual assault but sudden death to a loved one was most commonly reported by men. The number of traumatic events during the first 18 years of life was on average 7.3 traumas per person, 7.6 for women and 6.5 for men. Overall interpersonal traumas were more prevalent than non-interpersonal traumas with physical and sexual assault as the most prevalent types of traumas. Majority of participants (65,5%) reported severe PTSD symptoms (score >32) with average score of 40.6 on the PCL-5. Non-significant difference was on PTSD severity between males and females. This indicates that more than half of participants met the full diagnostic criteria for PTSD. Although most had informed a healthcare professional about their traumatic events ...